Another model of development is possible: questions on the economic moral in Prof. Luis González-Carvajal - Segovia Bernabé, José Luis (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
This article approaches the bibliographical production of Prof. Luis González-Carvajal from the perspective of the economic morality. Stands out his rigor and his synthetic and descriptive clarity of the macroeconomic reality. His more genuine contribution centres on the moment of «to «judge». It does it from an ethics always astride between «the Utopia and the reality», with an evangelical, very critical perspective with the neoliberalism, and formulating an authentic reading believer of the economic reality. For this moral judgment and for the later moment of «to operate» transformer, they are key categories very worked by the honoured one as social justice, political charity or structures of sin.
Keywords: Social justice; neoliberalism; political charity; structures of sin; economic crisis.